Agro-Industrial Residues: Eco-Friendly and Inexpensive Substrates for Microbial Pigments Production - Lopes, Fernanda Cortez; Ligabue-Braun, Rodrigo (Frontiers in Sustainable Food Systems, 2021)
Brazilian economy is one of the most important agriculture-based economies in the world, producing coffee, sugarcane, soybean, cassava, fruits and other commodities. This production is responsible for the generation of enormous amounts of daily residues, such as cassava and sugarcane bagasses, rice husk, and coffee peel. These residues are rich sources for renewable energy and can be used as substrates for industrial interest products. Microorganisms are useful biofactories, capable of producing important primary and secondary metabolites, including alcohol, enzymes, antibiotics, pigments, and many other molecules. The production of pigments was reported in bacteria, filamentous fungi, yeasts, and algae. These natural microbial pigments are very promising because synthetic colorants present a long history of allergies and toxicity. In addition, many natural pigments present other biological activities, such as antioxidant and antimicrobial that are interesting for industrial applications. The use of inexpensive substrates for the production of these metabolites is very attractive, considering that agro-industrial residues are generated in high amounts and usually are a problem to the industry. Therefore, in this article we review the production of microbial pigments using agro-industrial residues during this decade (2010-2020), considering both submerged and solid state fermentations, wild-type and genetically modified microorganisms, laboratorial to large-scale bioprocesses, and other possible biological activities related to these pigments.